Volar Plate Fixation Versus Cast Immobilization in Acceptably Reduced Intra-Articular Distal Radial Fractures: A Randomized Controlled Trial. (3rd November 2021) - Selles, C.A.; Mulders, M.A.M.; Winkelhagen, J.; van Eerten, P.V.; Goslings, J.C.; Schep, N.W.L.
Abstract : Background: The evidence for the treatment of acceptably reduced intra-articular distal radial fractures remains inconclusive. We therefore compared the functional outcomes of cast immobilization (nonoperative) and volar plate fixation (operative) for patients with these fractures. Methods: This multicenter randomized controlled trial enrolled patients between 18 and 75 years old with an acceptably reduced intra-articular distal radial fracture. Patients were randomized to nonoperative treatment or to operative treatment. The primary outcome measure was the Patient-Rated Wrist Evaluation (PRWE) score after 12 months. Secondary outcome measures were the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire; the Short Form-36 (SF-36) questionnaire; a visual analog scale for pain; range of motion; grip strength; radiographic parameters; and complications. Analyses followed the intention-to-treat principle. Results: A total of 96 patients were randomized, and 90 (46 in the nonoperative group and 44 in the operative group) were included in the analysis. Patients treated in the operative group had significantly better functional outcomes measured with the PRWE at 6 weeks, 3 months, 6 months, and 1 year. Additionally, a 28% rate of subsequent surgery was identified in the nonoperative group. Conclusions: Adult patients with an acceptably reduced intra-articular distal radial fracture have better functional outcomes for 12 months when treated operatively instead of nonoperatively. We therefore recommend surgical treatment for patients with these fractures. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.